Use of poly(o-toluidine)/ZrO2 nanocomposite coatings for the corrosion protection of mild steel - Chaudhari, Sudeshna; Patil, P. P.; Mandale, A. B.; Patil, K. R.; Sainkar, S. R. (Journal of Applied Polymer Science, 2007)
This study explored the possibility of using poly(o-toluidine) (POT)/ZrO2 nanocomposite coatings for the corrosion protection of mild steel in a chloride environment. POT/ZrO2 nanocomposite coatings were synthesized on steel substrates through an electrochemical route. These coatings were characterized with cyclic voltammetry, ultraviolet-visible absorption spectroscopy, Fourier transform infrared spectroscopy, scanning electron microscopy, and X-ray photoelectron spectroscopy. The performance of POT/ZrO2 nanocomposites as protective coatings against the corrosion of mild steel in aqueous 3 wt % NaCl was evaluated with the potentiodynamic polarization technique and electrochemical impedance spectroscopy. The results of this study demonstrate that POT/ZrO2 nanocomposite coatings provide better protection for mild steel against corrosion than pure POT coatings. The corrosion potential was about 0.312 V versus a saturated calomel electrode, more positive in aqueous 3 wt % NaCl for the nanocomposite-coated steel than the uncoated steel, and the corrosion rate of steel was reduced by a factor of almost 51. (c) 2007 Wiley Periodicals, Inc.
Keywords: Coatings; conjugated polymers; FTIR; Nanocomposites; synthesis